Debt restructuring through equity issues - Kim, Woojin; Ko, Young Kyung; Wang, Shu Feng (Journal of Banking and Finance, 2019)
This paper examines whether new equity may be issued to recapitalize existing assets in financially distressed firms. Using a sample of 3,184 follow-on primary common stock issues offered by Korean publicly traded firms from 2000–2013, we find that more than one-third of the equities are issued to creditors in direct exchange for debt. We also determine that equity issuers are in severe financial distress prior to the issue and are more likely to experience a subsequent change in control. The proceeds are used more to replace existing debt than to increase R&D. These findings suggest that equity issues in emerging markets may be used primarily to recapitalize existing assets through debt restructuring or control transfers rather than to finance growth options.
Keywords: Control transfer; Debt restructuring; Debt-equity swap; Distress; Emerging markets; Equity issue